Polyphenols of Perilla frutescens of the family Lamiaceae identified by tandem mass spectrometry - Razgonova, Mayya P.; Konkova, N. G.; Zakharenko, Alexander M.; Golokhvast, Kirill S. (Вавиловский журнал генетики и селекции)
Perilla frutescens is mainly cultivated as an oilseed crop. Perilla seeds contain 40-53 % of oil, 28 % of protein. The growing season is 100-150 days. In Russia, perilla is grown in the Far East, where the yield is 0.8-1.2 t/ha. Perilla of different geographical origin has its own special, sharply different features that characterize two geographical groups: Japanese and Korean-Chinese. These groups differ from each other in the length of the growing season, the height of plants, the color of the stem, the surface and the size of the leaves, the shape of the bush, the shape and size of the inflorescences, the size of the cups, the size and color of the seeds. P frutescens contains a large number of polyphenolic compounds that are biologically active components. The purpose of this research was a metabolomic study of extracts from leaves of P frutescens obtained from the collection of Federal Research Center the N.I. Vavilov All-Russian Institute of Plant Genetic Resources, grown on the fields of the Far East Experiment Station - Branch of Federal Research Center (Primorsky Krai, Russia). To identify target analytes in extracts, HPLC was used in combination with an ion trap. Preliminary results showed the presence of 23 biologically active compounds corresponding to P. frutescens. In addition to the reported metabolites, a number of metabolites were newly annotated in P. frutescens. There were hydroxycoumarin Umbelliferone; triterpene Squalene; omega-3 fatty acid Stearidonic [Moroctic] acid; higher-molecular-weight carboxylic acid: Tetracosenoic acid and Salvianic acid C; lignan Syringaresinol and cyclobutane lignan Sagerinic acid, etc. A wide range of biologically active compounds opens up rich opportunities for the creation of new drugs and dietary supplements based on extracts of perilla of the family Lamiaceae, subfamily Lamioideae, tribe Satureji and subtribe Perillinae.